The Effectiveness of Applying the Debate Method in Improving Students' Opinion Skills in PKN Class Va Subjects at Muder Teresa Catholic Elementary School, Kupang City - Bais, Debora; Marselina, Yulsy; Yunita Benu, Asti (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The Effectiveness of Applying the Debate Method in Improving Students' Opinion Skills in Civics Subjects, Class VA, Muder Teresa Catholic Elementary School, Kupang City. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Supervisors: (Yulsy Marselina Nitte, S.H., M.Pd and Asti Yunita Benu, S.Pd., M.Pd).The effectiveness of applying the debate method can improve students' ability to express opinions in Civics learning, which is one of the important subjects to be studied by students at elementary school level. It can be said that because Civics is a subject whose application is closely related to everyday life. This research aims to find out whether the application of the debate method can improve students' ability to express opinions in the Civics class VA subject at Muder Teresa Catholic Elementary School, Kupang City. This research method is a type of qualitative research with a description method. The collection instruments in this research are observation sheets, interview guides or question sheets.The results of this research show students' lack of courage in expressing their opinions. The lack of student courage is caused by several factors including internal and external factors, namely, lack of student motivation in expressing opinions, students are sometimes bored and do not pay attention to learning, students' lack of motivation when speaking in public. Meanwhile, efforts that can be made by teachers are, learning using the debate method, motivating students, debating strategies in learning so that they can help students have the courage to express their opinions.